The inter-unit and inter-model reliability of GNSS STATSports Apex and Viper units in measuring peak speed over 5, 10, 15, 20 and 30 meters - Beato, Marco; de Keijzer, Kevin (Biology of Sport, 2019)
The objective of this investigation was to evaluate the inter-unit reliability (Apex vs. Apex; Viper vs. Viper) and inter-model reliability (Apex vs. Viper) from 5 to 30 m sprinting activity. Ten team sport players (age 22 ± 1 years) were enrolled in this crossover study and performed 1271 trials (436 Apex vs. Apex, 464 Viper vs. Viper, 371 Apex vs. Viper) consisting of 5–10 m, 10–15 m, 15–20 m, and 20–30 m sprints. Interunit reliability was calculated using the intra-class correlation coefficient (ICC) with 95% confidence interval (CI) and coefficient of variation (CV), while between-unit and model analysis were subsequently performed to evaluate differences in Vpeak. Apex (10 Hz) units had excellent inter-unit reliability for all distances, whereas Viper (10 Hz) units had good to excellent reliability. The CV was good (< 5%) for both GNSS models. Significant differences were found in Vpeak in Sprint 5–10 = 0.13 CI (0.08, 0.182) m.s-1, Sprint 10–15 = 0.06 CI (0.01, 0.1) m.s-1, and in Sprint overall = 0.06 CI (0.03, 0.09) m.s-1. Both Viper and Apex units can consistently report Vpeak measurements since good to excellent ICC and good CV were found. However, Vpeak measurements are significantly different between models for distances less than 15 m. In conclusion, this study shows that differences exist among manufacturers’ models and that the two GNSS models should not be used interchangeably to quantify Vpeak.